Analisa Tampungan Drainase Pengendalian Banjir Sungai Lambidaro - Sekanak Kota Palembang (Studi Kasus Jembatan Letnan Mukmin - Jembatan Tua Patih Naya Raya) - Junaina, Eka; Sahbar, Robi; Ramadhani, Ramadhani (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Population growth in Palembang City has put pressure on the fulfillment of housing needs, industrial/service areas and supporting facilities which have caused land that was previously a conservation area, water catchment area, to turn into watertight areas which have caused increased water flow from an area which causes puddles and floods which tend to increase over time, coupled with the geographical conditions of Palembang City with rainfall during 2022 ranging from 97.2 mm (July) to 47.30 mm (January), and has relatively high air humidity where the average ranges from 81.00% to 84.30% in March so that Palembang City is highly likely to experience frequent rain. There are 19 (nineteen) flood control drainage systems in Palembang City, one of which is the Lambidaro and Sekanak river drainage subsystems. The purpose of this study was to determine the storage capacity of the Lambidaro-Sekanak River flood control drainage channel for the next 5-year return period.The required data included the existing condition of the Lambidaro-Sekanak River flood control drainage channel, rainfall data, and other specifications related to the test results.The analysis revealed that the drainage capacity for the 5-year return period was 10,116 m3/s